L'École de Paris ? 1945-1964 : Fondation Musée d'Art Moderne Grand-Duc Jean Préfiguration du Musée. - Ceysson, Bernard; Daval, Jean-Luc; Santer, Jacques; Wilson, Sarah; Fondation Musée d'Art Moderne Grand-Duc Jean (Luxembourg : Musée National d'Histoire et d'Art, 1998)
Agam, Yaacov ; Al-Coat ; Alechinsky, Pierre ; Appel, Karel ; Arden Quin, Carmelo ; Arman ; Arp, Hans (Jean) ; Artaud, Antonin ; Atlan, Jean-Michel ; Baertling, Olle ; Balthus ; Barré, Martin ; Bazaine, Jean ; Bissière, Roger ; Brauner, Victor ; Bryen, Camille ; Bury, Pol ; Calder, Alexander ; César ; Chaissac, Gaston ; Debré, Olivier ; Dewasne, Jean ; Deyrolle, Jean ; Dias, Cicero ; Domela, César ; Doucet, Jacques ; Dubuffet, Jean ; Dufrêne, François ; Equipo 57 ; Estève, Maurice ; Etienne-Martin ; Falkenstein, Claire ; Fautrier, Jean ; Feito, Luis ; Fernandez, Luis ; Fougeron, André ; Francis, Sam ; Giacometti, Alberto ; Gilioli, Emile ; Gorin, Jean ; Gruber, Francis ; Hajdu, Etienne ; Hans, Raymond ; Hantaï, Simon ; Hartung, Hans ; Hausmann, Raoul ; Hayter, Stanley William ; Hélion, Jean ; Herbin, Auguste ; Herold, Jacques ; Heurtaux, André ; Isou, Isidore ; Jacobsen, Robert ; Jorn, Asger ; Kelly, Ellsworth ; Kemeny, Zoltan ; Klein, Yves ; Lam, Wifredo ; Lapicque, Charles ; Lardera, Berto ; Leger, Fernand ; Manessier, Alfred ; Mangelli, Alberto ; Marle, Félix Del ; Masson, Andre ; Mathieu, Georges ; Matisse, Henri ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Michaux, Henri ; Moal, Jean Le ; Morellet, François ; Mortensen, Richard ; Nemours, Aurélie ; Ossorio, Alfonso ; Pan, Marta ; Pevsner, Antoine ; Picabia, Francis ; Picasso, Pablo ; Pignon, Edouard ; Poliakoff, Serge ; Raymond, Marie ; Raysse, Martial ; Réquichot, Bernard ; Richier, Germaine ; Riopelle, Jean-Paul ; Saura, Antonio ; Schneider, Gérard ; Schoffer, Nicolas ; Shiraga, Kazuo ; Sima, Josef ; Singier, Gustave ; Soto, Jesus Rafael ; Soulages, Pierre ; de Staël, Nicolas ; Szenes, Arpad ; Tàpies, Antoni ; Tinguely, Jean ; Tobey, Mark ; Ubac, Raoul ; Vasarely, Victor ; etc.
biografie
L'École de Paris ? 1945-1964, Musée National d'Histoire et d'Art, Luxembourg, 12 décembre 1998 - 21 février 1999
Frans & Engels
boek